2012
DOI: 10.1021/nn204491q
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Monolayer and Bilayer Membranes Made From Amphiphilic Block Copolymer Micelles

Abstract: The deposition of amphiphilic poly(ethylene oxide)-block-poly(butadiene) (PEO-b-PBD) copolymer micelles is demonstrated on solid substrates. Depending upon surface chemistry, micelle adsorption creates either monolayer or bilayer films. Lateral diffusion measurements reveal that strong coupling between hydrophilic surfaces and PEO blocks creates immobile bilayers, while monolayers retain the fluidity previously observed in vesicular assemblies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(56 citation statements)
references
References 38 publications
6
47
3
Order By: Relevance
“…By contrast, this effect was not observed in a lipid-based system containing BODIPY-HPC and BC-1 for which solution-based lipid vesicles had comparable ETE to supported lipid bilayers (see Table S4 PBD monolayers have lateral mobility comparable to the same dye in lipid membranes. 27 These mobility patterns for BODIPY-HPC in bilayer and monolayer samples were also observed in the current study, but with an additional interesting optical response due to the presence or absence of the BC-1 acceptor. For polymer bilayers, bleaching of BODIPY led to no FRAP recovery ( Figure 4A), as expected, however, preferential bleaching of BC-1 caused an increased BODIPY fluorescence intensity in the 'bleach region' (Figure 4C).…”
Section: Figure 3 Energy-transfer Efficiency Of Polymer/chromophore supporting
confidence: 84%
See 4 more Smart Citations
“…By contrast, this effect was not observed in a lipid-based system containing BODIPY-HPC and BC-1 for which solution-based lipid vesicles had comparable ETE to supported lipid bilayers (see Table S4 PBD monolayers have lateral mobility comparable to the same dye in lipid membranes. 27 These mobility patterns for BODIPY-HPC in bilayer and monolayer samples were also observed in the current study, but with an additional interesting optical response due to the presence or absence of the BC-1 acceptor. For polymer bilayers, bleaching of BODIPY led to no FRAP recovery ( Figure 4A), as expected, however, preferential bleaching of BC-1 caused an increased BODIPY fluorescence intensity in the 'bleach region' (Figure 4C).…”
Section: Figure 3 Energy-transfer Efficiency Of Polymer/chromophore supporting
confidence: 84%
“…27 Static We found that PEO-b-PBD/chromophore nanocomposites could be assembled with any donor or acceptor concentration up to ~3% (chromophore mol% relative to polymer concentration) before chromophore aggregation effects were observed. Therefore, for detailed characterization, we generated sets of samples at chromophore concentrations that exhibited good energy transfer (10-60% efficiency) and no observed aggregation.…”
Section: Textmentioning
confidence: 81%
See 3 more Smart Citations